CNT modified layered α-MnO2 hybrid flame retardants: preparation and their performance in the flame retardancy of epoxy resins. Issue 46 (21st July 2020) - Qian, Xiaodong; Shi, Congling; Jing, Jingyun
Abstract : In this paper, CNT modified layered α-MnO2 hybrid flame retardants (α-MnO2 –CNTs) were synthesized through one-pot preparation. Abstract : In this paper, CNT modified layered α-MnO2 hybrid flame retardants (α-MnO2 –CNTs) were synthesized through one-pot preparation. The structure and composition of the α-MnO2 –CNTs hybrid flame retardants were investigated by X-ray diffraction, TEM and SEM. Subsequently, the α-MnO2 –CNTs hybrids were then incorporated into epoxy resin (EP) to improve the fire safety properties. Compared with pure EP and the composites with CNTs or α-MnO2, EP/α-MnO2 –CNTs composites exhibited improved flame retardancy and smoke suppression properties. With the incorporation of only 2.0 wt% of α-MnO2 –CNTs hybrid flame retardants, the peak heat release rate and total heat release of the composites showed 34% and 10.7% reduction respectively. In addition, the volatile gases such as CO and CO2 were reduced and the smoke generation was also effectively inhibited. The improved fire safety of the composites is generally due to the network structures and the synergistic effect of α-MnO2 and CNTs, the catalyzing charring effect, smoke suppression and the physical barrier effect of α-MnO2 nanosheets.